Bioavailability of caffeic acid in rats and its absorption properties in the Caco-2 cell model. (September 2014) - Wang, Su-Jun; Zeng, Jie; Yang, Ben-Kun; Zhong, Yun-Ming
Abstract Context: Caffeic acid (CA) is widely distributed in edible plants, and it is beneficial to human health by exerting various biological effects. The potential pharmacological activities of CA are dependent on its absorption in the gastrointestinal tract. Objective: To investigate the bioavailability of CA in rats and its absorption properties in the Caco-2 cell model. Materials and methods: A sensitive LC-MS/MS method was successfully applied to determine CA in rat plasma, perfusate, and Hank's balanced salt solution (HBSS). The absolute bioavailability (Fabs) of CA was obtained after i.v. (2 mg/kg) or i.g. administration (10 mg/kg) to rats. Blood samples (approximately 250 µL) were collected from the jugular vein catheter. Pharmacokinetic parameters were calculated using the 3P97 software (version 2.0 PK software; Chinese Society of Mathematical Pharmacology, Anhui, China). The intestinal absorption of CA was explored by the in situ vascularly perfused rat intestinal preparation. CA (5 mg/kg) was administered into the duodenum. Samples (250 µL) were collected from reservoir at specific times, and the same volume fresh perfusate was replaced. The Caco-2 cell model was applied to measure the permeability of CA from the apical to basolateral side (A → B) and from the basolateral to apical side (B → A). Results: The absolute bioavailability (Fabs) of CA was 14.7%, and its intestinal absorption was 12.4%. The Papp A→B values of CA were ranging from (4.87 ± 1.72) × 10−7 cm/s to (5.05 ± 0.66) × 10−7 cm/s as the concentration varied from 5 to 15 µg/mL. Conclusion: CA was shown to have low oral bioavailability in rats, low intestinal absorption, and poor permeability across Caco-2 cells.